The exporter wage premium reconsidered destinations, distances and linked employer-employee data - Achim Schmillen (Osteuropa-Institut Regensburg, 2011)
This study uses detailed, reliable and up-to-date linked employer-employee data that take account of both the demand and the supply side of the labor market to challenge the conventional wisdom of a universal exporter wage premium. It investigates whether for German establishments an exporter wage premium can be found irrespective of export destination and the distance between export origin and destination. As expected, it finds that exporters generally pay higher wages than non-exporters. But it also shows that only exporting to certain countries is associated with a wage premium. Moreover, such a premium exists only for establishments that ship goods over a relatively long distance.
Keywords: F14; J31; 330; Exporter wage premium; Export destinations; Linked employer-employee data; Exportindustrie; Lohnstruktur; Unternehmen; Schätzung; Deutschland; Auslandsmarkt; Entfernung